Biosynthesis of Low Relative Molecular Mass Bacterial Cellulose in Presence of D-xylose - Han, Yali; Liu, Haifang; Zhang, Mingnan; Feng, Yuhong (Asian Journal of Chemistry, 2015)
Acetobacter xylinum strain was screened in our own laboratory. It can used several saccharides as carbon source. Coconut water was adapted as incubating system. Bacterial cellulose was biosynthesized by static fermentation culture. Low relative molecular mass bacterial cellulose was obtained when D-xylose was added into the medium, which water-holding capacity, structure features, crystallization properties, thermal decomposition behaviours of the bacterial cellulose almost have no difference compared with pure bacterial cellulose. But the molecular mass of product is lower than that of pure bacterial cellulose. D-xylose maybe used as sealing carbon source.